Viral Encephalomyelitis Features of the Course and Outcomes - Khojimatova Malika Shukhratovna (Zien Journals, 2021)
Encephalomyelitis is an inflammation of the substance of the brain and spinal cord, which can develop under the influence of various factors, while manifesting approximately the same cerebral, focal symptoms. Today, the problem of encephalomyelitis and inflammatory diseases of the nervous system in general remains relevant, especially in our region, since not all patients are aware of the severity and outcome of these diseases
Keywords: Inflammation; neurological; neuroimaging; immunological features